EVALUATION OF THE EFFICACY AND SAFETY OF THE ART REGIMENS CONTAINING LOW DOSES PHOSPHAZID - N. V. Sizova; I. O. Modestova; F. F. Shakhova; N. V. Koplevskaya; O. A. Klitsenko; A. V. Kravchenko; O. G. Yurin; D. A. Gusev (Журнал инфектологии)
In 20 patients, treated with regime of ART including phosphazid at a dose of 800 mg/day, his daily dose was reduced to 400 mg. In 19 of 20 patients the phosphazod’ dose reduction was due to the development of adverse events related to therapy. After changing the phosphazid’ daily dose the patients seen during the 1 year. Lowering the phosphazid’ dose did not lead to virological failure of the regime of ART and/ or progression of HIV-infection. On the background of lower doses in almost all patients observed a significant improvement in health- the reduction of weakness, disappearance of nausea and headaches. The analysis of laboratory data through 48 weeks after the change daily dose of the phosphazid also showed improvement in these indicators.